How do real Indigenous forest dwellers live? Neoliberal conservation in Oaxaca, Mexico - Altamirano-Jiménez, Isabel (Atlantis, 2017)
Protected areas such as wildlife sanctuaries, national parks, and forest reserves have become an important feature of the global economy. Using an intersectional lens, a critical political economy approach, and document analysis, this paper explores how power operates through the production of Indigenous difference, the greening of the economy, and the commodification of the environment. It also considers neoliberal conservation as a racialized process that downloads the burden of protecting the environment onto the most vulnerable Indigenous communities.